1978
DOI: 10.1128/aac.13.3.484
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of cephalothin-resistant gram-negative bacilli to piperacillin, cefuroxime, and other selected antibiotics

Abstract: The in vitro antibacterial activity of piperacillin and cefuroxime against 180 isolates of cephalothin-resistant Enterobacteriaceae and of piperacillin against 46 isolates of Pseudomonas aeruginosa was determined. Amikacin, gentamicin, carbenicillin, cefoxitin, and cefamandole were included for comparison. The activities of piperacillin and carbenicillin against Enterobacteriaceae were comparable. Piperacillin was appreciably more active against Pseudomonas than carbenicillin and was equivalent in activity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
8
0

Year Published

1978
1978
1987
1987

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…Previous reports have also shown that moxalactam (2) and ceftriaxone (12) but not piperacillin (6,10) …”
mentioning
confidence: 90%
“…Previous reports have also shown that moxalactam (2) and ceftriaxone (12) but not piperacillin (6,10) …”
mentioning
confidence: 90%
“…At a concentration of 12.5 jig/ml, 83% of the isolates were inhibited with PIP, compared to 4 and 2% with TIC and CARB, respectively. A concentration of -200 ,ug of CARB or TIC per ml was required to inhibit 14 isolates, 13 of which were inhibited by PIP at a concentration of at least 25 ,ug/ml.…”
mentioning
confidence: 93%
“…Piperacillin (T-1220) (PIP) is a new semisynthetic derivative of aminobenzyl-penicillin with a broad spectrum of antimicrobial activity, which particularly is more active than either carbenicillin (CARB) or ticarcillin (TIC) against Pseudomonas aeruginosa (3)(4)(5)(6)(7). In the study reported here, the in vitro activities of PIP, CARB, and TIC in combination with gentamicin (GM), tobramycin (TM), and amikacin (AM) against 54 isolates of P. aeruginosa were compared.…”
mentioning
confidence: 99%
“…830,1979). In vitro and in vivo studies demonstrate that piperacilHin has a broad spectrum of activity (5,7,12,13). It is effective against most gram-positive and gram-negative organisms, including anerobes.…”
mentioning
confidence: 99%